What Works to Retain Beginning Teachers in the Profession? A Mixed Methods Approach to Detect Determining Factors - Muhammet Safa Göregen; Els Tanghe; Wouter Schelfhout (Education Sciences)
This study investigates the determinants of teacher retention, focusing on the Flemish region of Belgium, where early-career teacher attrition presents a significant challenge. Employing a mixed methods approach, the research combines quantitative survey data (N = 133) and qualitative interviews (N = 12) to examine variables related to initial guidance (general support, learning and sharing with colleagues, mentoring) and the supportive school context (sense of belonging at school, cooperation, clear goals and support, appreciative school leadership). The findings demonstrate that key elements within the supportive school context—particularly sense of belonging, cooperation, clear goals, and appreciative leadership—have a positive influence on teacher retention. Conversely, general support within initial guidance exhibits a comparatively weaker predictive value. The qualitative analysis reveals inconsistencies in the provision and quality of initial guidance support across schools, which adversely impacts teachers’ professional integration and job satisfaction. The study concludes that the implementation of structured support systems, well-defined goals, and appreciative leadership are critical for improving retention rates. These findings underscore the necessity for schools to adopt both individualized and institutional strategies to address early-career teacher attrition effectively.